Закордонний досвід забезпечення конкурентоспроможного розвитку фермерських господарств - Єременко, Денис Володимирович; Еременко, Денис Владимирович; Yeremenko, Denys (Мелітополь: Вид-во Мелітопольська типографія «Люкс», 2016)
UK: В статті проаналізовано особливості закордонного розвитку фермерських господарств як складової аграрного підприємництва. Відмічається унікальний характер становлення вітчизняного фермерства як складової аграрного виробництва. Проаналізовано сучасні проблеми розвитку фермерських господарств з урахуванням закордонного досвіду їхнього вирішення. EN: The article analyzes the peculiarities of foreign farms as part of the agricultural business. Checked unique character formation of domestic farming as part of agricultural production. Analyzes the current problems of farmers on the basis of foreign experience to solve them. Noted the important role of public institutions to ensure the effective functioning of small agricultural enterprise system by implementing legal and organizational measures to improve their competitiveness. It is claimed that one of the important outstanding issues is to diversify domestic production farms. There are the following aspects of the diversification of economic activities of farms, diversification as a process of weakening depending on the results of agricultural activity; diversification as part of raising the level of support for farmers; diversification as an indicator of rural development; diversification leads to the production of various commodities, goods, services and protection from the impact of lower demand for certain goods; Diversification as a shock to the increase of the total family income of agricultural producers. An essential prerequisite for the development of competitive farms in accordance with the developed countries is the active use of information resources as a valuable means of production. Unfortunately, a common problem of domestic small agricultural enterprise is insufficient information support system mismatch training and economic realities. Addressing this issue involves the joint efforts of both government institutions and regional scientific and educational centers, as well as representatives of business community.
Foreign experience of support competitive farms
Keywords: фермерські господарства; аграрне виробництво; підприємницька діяльність; закордонний досвід; farms; agricultural production; entrepreneurship; foreign experience